From Islamic Ethics to State Indicators: Wasaṭiyah and the Bureaucratization of Religious Moderation in Indonesia - Musyafa Syamil Arroyan; Rasheed Adeyinka Uthman (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This article studies how Indonesian state documents on religious moderation, published between 2019 and 2024, turn the Islamic ethical concept of Wasaṭiyahinto administrative language. In Islamic thought, Wasaṭiyahmeans balance, justice, and the middle path. In Indonesian policy, religious moderation now appears as indicators, roadmaps, training programs, and evaluation procedures. The study uses qualitative library research and critical document analysis to read a set of official texts, including Ministry of Religious Affairs publications, national planning documents, ministerial regulations, and Presidential Regulation No. 58 of 2023. It does not ask whether these policies succeed or fail. Instead, it asks how official texts define acceptable religiosity and how that definition becomes something the state can govern. The main argument is that the state turns Wasaṭiyahfrom a broad ethical ideal into a bureaucratic framework built on four indicators: national commitment, tolerance, anti-violence, and accommodation of local culture. Through this process, the documents picture an ideal religious citizen who is loyal to the nation, tolerant, non-violent, and open to local culture. They also mark out an “immoderate” other, linked to extremism, intolerance, and anti-national attitudes.